Computers in Banking - Adewunmi Wole; Akinlade Titi (Lagos: Nigerian Institute of Bankers, 1988)
This book examines the application of computers for banking operations in Nigeria covering topics like: Basic data processing concepts; the status of computer application in commercial banks in Nigeria; development of computer-based management information systems for banks; operating a computer-based management information system; cost benefits of computerising banks; facilities for the development of information systems in banking.
uaa 22/01/19
Loans.
Keywords: Computer